(untitled) (International Journal of Physiotherapy, 2016)
Background: Functional impairment is one of the complicated mechanisms which reflect an association between the different aspects of a person’s body parts and features of the community of knowledge, behavior and intervention. Around 10 % of people around the world are estimated as functional impairment. The aim of this study is to explore the level of understanding and awareness about the functional limitations and their observations in the common people as well as to uncover the provision of medical facilitations for functionally impaired people in rural areas. Method: This study was conducted in Larkana and Mirpurkhas districts of Sindh, Pakistan. It was carried out from August 2013 to December 2013. It was a cross sectional survey study in which around 102 participants were recruited. A self formulated questionnaire was implemented to assess the knowledge, attitude and practice regarding physical limitations. Results: Results Indicates 71.6% respondents have knowledge regarding to functional limitations or impairments whereas 42.2% views it a settlement to one’s sins from Almighty super power. The second aspect of this study in which we wanted to disclose the factors of medical negligence and improper facilitations in which we found out that 85.3% people recommended that government should take serious actions to open more Rehabilitation centers. Conclusion: This study helped us to generate recommendations to make people aware about the increasing ratio of functional disabilities and to highlight the root causes. On the basis of this study we also introduced the concept of community based rehabilitation services as well.